The Influence of Father Involvement on the Perception of Well-being of Early Childhood Based on Parenting Style - Waningsih, Putri; Formen, Ali; Pranoto, Yuli Kurniawati Sugiyo (JURNAL PENDIDIKAN USIA DINI, 2025)
This study aims to identify the influence of father involvement on fathers' perceptions of the well-being status of early childhood children in terms of fathering style in Argomulyo District, Salatiga. This type of research is qualitative research. 136 fathers who participated in this study were selected through purposive sampling techniques based on specific respondent criteria. Data collection was carried out through questionnaires distributed offline to fathers. The data obtained were analyzed through multiple linear regression analysis techniques. The results of this study showed that father involvement influenced fathers' perceptions of their children's well-being status. However, there was no significant influence between father involvement and father’s perceptions of their children's well-being status when controlling for fathering style. However, father involvement was influenced by fathering style. Based on the father's parenting style, there was a significant difference in the father’s involvement and his perception of the child's well-being status. Father involvement and father's perceptions of the child's well-being status were dominated by an authoritative parenting style. This finding implies that there needs to be promotion and investment to support the improvement of children's well-being through the involvement of fathers, families, schools, and policies that support this.